Communication Acoustics - Blauert, Jens (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Communication Acoustics deals with the fundamentals of those areas of acoustics which are related to modern communication technologies. Due to the advent of digital signal processing and recording in acoustics, these areas have enjoyed an enormous upswing during the last 4 decades. The book chapters represent review articles covering the most relevant areas of the field. They are written with the goal of providing students with comprehensive introductions. Further they offer a supply of numerous references to the relevant literature. Besides its usefulness as a textbook, this will make the book a source of valuable information for those who want to improve or refresh their knowledge in the field of communication acoustics - and to work their way deeper into it. Due to its interdisciplinary character Communication Acoustics is bound to attract readers from many different areas, such as: acoustics, cognitive science, speech science, and communication technology.